Measuring business process performance in the seed industry - Goran Petrović (Anali Ekonomskog fakulteta u Subotici, 2020)
The literature that generally deals with business processes is extensive, but, at the same time, there is a noticeable lack of it in some specific areas, such as the seed industry. The paper presents the relations between the main participants in the process of creating new values and gives examples of business success indicators in the organization operating in the seed industry. The presented results are based on the author's research through questionnaires and interviews with employees in this field, while the aim of the research was to review business processes in the seed industry, identify the key ones, and determine the models for their performance management.